PERFORMANCE ASSESSMENT OF THE SELF-SERVICE QUEUING SYSTEMSTUDY CASE: PERTAMINA GAS STATION DAGO BANDUNG - Ermawan, Aria Rizki; Handayati, Yuanita (Journal of Business and Management, 2018)
Abstract. There are a strong relationship between managing queue performance and customer satisfaction. Customer tends to choose a place with less queue rather than a place with a long queue by assumes that the place offers the same value. For this reason, many businesses often manage their queueing performance effectively to create competitive advantage. Within this condition the firm must come up with effective solution to deal with their queue condition. Self-service system is a queueing model that allow customer to process their order without having employee or operator to process the order. In many case the implementation of self-service system is uses to overcome the long queue problem by maximizing server utilization. In June 2017, Pertamina gas station Dago Bandung is the first gas station in Bandung that has been implementing the self-service system for motorcycle gasoline refueling area. The implementation of a self-service system aims to overcome the queueing problem when peak hour at the motorcycle queueing area. However, after the implementation, the self-service system still has a long queue. Within this condition, the system needs to evaluate whether the self-service system is effective to overcome the queueing problem when peak hour or not. The result from this study shows that the queueing performance of the self-service system has a bottleneck on phase 1. But, compared to the non-self-service system, the overall performance of the self-service system has a better performance than the non-self-service system. This study recommends the firm to add one more server in phase 1 of the self-service system to overcome the bottleneck. Also, the researcher show queueing performance comparison between both of the system by assuming if the firm stick with the non-self-service system by increasing the number of servers.Keywords: Queuing line, Queuing Assessment, Self-Service System, Comparison